1990
DOI: 10.1203/00006450-199004000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Collagen-Induced Activation in the Newborn Platelet

Abstract: ABSTRACT. We have investigated the impaired secretion response of neonatal platelets. We compared the response of washed neonatal and adult platelets to thrombin and collagen, and to specific activators of calcium flux (inositol trisphosphate) and protein kinase C activation (oleoylacetyl glycerol). Neonatal platelets show no impairment ofaggregation, secretion of ['4C]serotonin or phosphorylation of saecific intracellular rotei ins in resDonse to thrombin. inositol trisphosphate, o; oleoyl-acetyl glycerol. ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 21 publications
1
60
0
Order By: Relevance
“…There is an apparent contrast between results from conventional platelet aggregation assays that suggest an in vitro hypofunctional state of neonatal platelets [1][2][3] and the evidence of normal or even short in vivo bleeding times of the newborn [4] , which is a suitable test for assessing primary hemostasis [5] .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…There is an apparent contrast between results from conventional platelet aggregation assays that suggest an in vitro hypofunctional state of neonatal platelets [1][2][3] and the evidence of normal or even short in vivo bleeding times of the newborn [4] , which is a suitable test for assessing primary hemostasis [5] .…”
Section: Introductionmentioning
confidence: 90%
“…Herein, we present an in vitro model that might help to explain the clinically observed short bleeding times in neonates despite in vitro hypoaggregable platelets reported in various studies [1][2][3]19] . We found that aggregation of neonatal platelets in WB samples is as efficient as that of adult platelets when the physiological relevant activator collagen/endogenous thrombin is used.…”
Section: Discussionmentioning
confidence: 99%
“…No difference was reported between neonatal platelet (derived from either cord or peripheral blood) and adult platelet delta granule release, as assessed by measurement of serotonin secretion, in response to stimulation with thrombin or the platelet agonists 1-oleolyl-2-acetyl-glycerol and inositol triphosphate (IP 3 ). However, serotonin secretion was markedly decreased in cord blood-derived neonatal platelets in response to collagen as compared to adult platelets (9). Further, as measured by mepacrine uptake, neonatal platelets (from cord blood) contained the same number of dense granules as adult platelets, but these same platelets had defective release of dense granules following thrombin stimulation (14).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have found that platelets of healthy term newborns are hyporeactive [14,15] and demonstrated impaired capability of GPIIb/IIIa complex activation [16] , whereas others have revealed that they respond to agonists as well as in adults [17] . This controversy may result from different time of blood sample collecting.…”
Section: Discussionmentioning
confidence: 99%